PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI DI SD NEGERI 63 BANDA ACEH - Diansari, Diansari; Hudallah, Noor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are among the fundamental competencies that have not yet developed optimally among elementary school students, as reflected in the decline in academic achievement at SD Negeri 63 Banda Aceh. This study aims to analyze the influence of the family and school environments on students’ critical thinking skills, with learning motivation as a mediating variable. The study employed a quantitative approach with an ex post facto design, involving 90 students in grades 4, 5, and 6 selected through saturation sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0, including a bootstrapping procedure with 5,000 subsamples. The results of the study indicate that the family environment (β = 0.121; p = 0.238) and the school environment (β = 0.173; p = 0.086) do not have a significant direct effect on students’ critical thinking skills, while both have a positive and significant effect on learning motivation (β = 0.598; p < 0.001 and β = 0.455; p < 0.001), and learning motivation has a positive and significant effect on students’ critical thinking skills (β = 0.492; p < 0.001). Learning motivation was found to partially mediate the effects of both the family environment (indirect effect = 0.285; p = 0.001; VAF = 70.2%) and the school environment (indirect effect = 0.217; p = 0.002; VAF = 55.6%) on critical thinking skills. These findings indicate that learning motivation serves as a key mechanism bridging the influence of external environmental factors on students’ critical thinking skills.